Pengembangan Sistem Monitoring Dan Prediksi Cuaca Maritim Untuk Peningkatan Keselamatan Navigasi - Dian Minarto; Kurniawan Teguh Santoso (Institut Nalanda, 2023)
The unpredictability of maritime weather has long been a significant challenge in ensuring the safety of maritime navigation and maritime operations in general. In an effort to address this issue, this research focuses on the development of an innovative maritime weather monitoring and prediction system. The proposed system leverages advanced technologies such as weather sensor networks, satellite monitoring, and real-time data analysis to provide accurate and real-time weather information to the maritime community. With improved access to weather data, ships, ports, and relevant stakeholders can make more timely and informed decisions when planning operations, reducing the risk of maritime accidents, and enhancing navigation efficiency. Furthermore, the system is equipped with sophisticated weather prediction algorithms, enabling weather forecasts for several days ahead. This capability offers additional advantages to maritime operators, allowing them to plan routes, cargo handling operations, and fleet management more effectively. The results of this research represent a significant contribution to enhancing navigation safety and maritime operational efficiency. By combining modern technology with scientific knowledge of maritime weather, this system provides a reliable solution for addressing weather challenges at sea, potentially saving lives and reducing economic losses resulting from maritime accidents.